Determinants of Performance Arena of Ḍeuḍā and their Cultural Implications - Air, Narendra Bahadur (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2025)
This article explores Ḍeuḍā, a traditional folk song prominent in Sudurpashchim province, emphasizing its cultural significance and the pivotal role of performance in realizing its essence. The performance arena of Ḍeuḍā transcends mere location, encompassing the interplay of performers, audience, and contextual conditions. It posits that Ḍeuḍā achieves its fullest expression through active performance, with the performers’ skill, the audience’s engagement, and the setting collectively shaping the experience. The study reflects upon the performance theory and attempts to make an assessment of it in relation to the Deudā song that adopts qualitative research method, using observations and interviews as data collections tools. This study examines Ḍeuḍā performance as a socially situated art, involving the active participation of both performers and audience to co creates meaning. The study also investigates the three primary theaters where Ḍeuḍā is performed: intimate (natural spaces), private/domestic (family-centered), and public (festivals and fairs), each contributing distinct dynamics to the performance styles and themes. The article delves into how these arenas influence the performance’s thematic expressions ranging from love and personal reflection to communal values and social commentary. By situating Ḍeuḍā within its cultural, social, and performative frameworks, the study underscores its role as an aesthetic and communicative medium, deeply rooted in the collective identity and traditions of Sudurpaschim. The findings of the study reveal that the performance arena of Ḍeuḍā serves as the focal point where the event takes place. The song achieves its full expression through performance, meaning it may be best understood and appreciated when performed. The interplay between the performer, the art form, the audience, and the setting are essential for Ḍeuḍā performance. The performance arena of Ḍeuḍā encompasses the location or setting, the events, personal and collective conditions, and the nature of its genesis.